The effect of using a learning how to learn model on the achievement of biological concepts and the development of learning and study strategies for second grade female students is average (Journal of the College of Basic Education, 2022)
Today, the world is facing a broad knowledge and information explosion that requires the individual to keep up, and for this reason, education has tended to accustom students to independence in their learning, because its programs are no longer able to provide learners with only the basics and principles of knowledge.Therefore, the current study aimed to:1- Measuring the impact of the learning how to learn model on the achievement of biological concepts among the female students of the research sample.2- Measuring the impact of the learning how to learn model on developing learning and study strategies among the female students of the research sample.In order to achieve the objectives of the research, the following zero hypotheses were set:1- There is no statistically significant difference at the level of significance (0.05) between the average scores of the students of the experimental group who studied using the learning how to learn model and the average scores of the control group who studied without using the learning how to learn model in the biological concepts achievement test.2- There is no statistically significant difference at the level of significance (0.05) between the average differences of the scores of the students of the experimental group who studied using the learning how to learn model and the average differences of the degrees of the students of the control group who studied without using the learning how to learn model in the pre and post learning and study strategies scale.